Kontak bahasa dalam lanskap linguistik di Kota Bandar Lampung - Fadillah, Arif (Aksara: Jurnal Bahasa dan Sastra, 2023)
This research aims to describe the forms of language phenomena such as monolingual, bilingual, and multilingual in the linguistic landscape of Bandar Lampung city. As one of the major cities in Sumatra, Bandar Lampung is a melting pot of various communities with different backgrounds. Bandar Lampung is also a student city in Lampung Province, which leads to language contact phenomena that arise in Bandar Lampung. The Linguistic Landscape can be used to observe these phenomena. This research is qualitative in nature, and data is obtained from observations made through the Google Maps application. The data collection technique used is note-taking and observation. Data analysis techniques used in this research include data collection, data reduction, data presentation, and concluding. The results of this research indicate the presence of monolingual, bilingual, and multilingual forms in the linguistic landscape of Bandar Lampung. These forms can be seen in syntactic structures such as words, phrases, clauses, and even sentences. The emergence of these three forms is influenced by economic, religious, ethnic, and educational factors. In this research, the researcher restricted the data collection to texts outside of enclosed spaces.Keywords: Bandar Lampung City, bilingual, linguistic landscape, monolingual, multilingual